In vitro and In vivo assessment of Gelatin nanoparticles loaded doxocetal scaffolds - Patel, Arun Kumar (International Journal of Pharmaceutical & Biological Archive, 2017)
Aim: The aim of this study to evaluates the physiochemical properties, drug loading, in vitro release, antibacterial and wound healing activity. Gelatin is a common natural polymer or protein which is normally produced by denaturing collagen. It has been used in pharmaceutical and medical applications due to its outstanding properties such as biodegradability, biocompatibility, and low antigenicity. Materials and Methods: Docetaxel -loaded gelatin nanoparticles by using UV-Vis spectroscopy, XRD, Particle size and size distribution, Scanning electron microscopy (SEM), Drug entrapment efficiency, Differential scanning caloriemetry (DSC) and EDX were characterized. Wound healing activity was determined on Wistar rats using excision wound models. Results: Solubility, crystallinity, and the crystal properties of an active pharmaceutical ingredient (API) play a critical role in the value chain of pharmaceutical development, manufacturing, and formulation.. The rate of drug release for formulation stored at 45Â±10C was increased as compared with the fresh formulation; it might be due to the formation of more pores in the nanoparticles due to evaporation of residual amount of solvent. Studies on docetaxel-loaded gelatin nanoparticles-impregnated ointment for its wound healing property on excised wound showed significant results in terms of epithelialization period and wound contraction and was close to the standard (Povidone iodine ointment) used. Conclusion: The antibacterial activities and sorption capacities of the Docetaxel -loaded gelatin nanoparticles are strong indicators to their in vivo functionalities as wound dressing.